Kahweol and cafestol in coffee brews: comparison of preparation methods (Revista Ciência Agronômica, 2019)
The profile of bioactive compounds in coffee brews depends on the coffee bean species and varieties,harvesting and post-harvesting practices, roasting processes, and also on the brewing method. The present researchaimed to study the contents of cafestol and kahweol - coffee diterpenes with a known impact on human health –comparing coffee beverages prepared using common brewing methods (filtered, espresso, and instant coffee brews).Filtered (cloth-filtered and paper-filtered), espresso and instant brews were obtained from a medium-roasted Coffeaarabica coffee (NY 2). Five genuine replicates of each coffee brew were prepared, and the extracts were lyophilized. Avalidated UPLC-based method provided the content of diterpenes. The results were reported in mg of diterpene per g ofsolids or per a standard dose of 50 mL of coffee brew. Solids content of coffee brews ranged from 2.06 to 2.46 g 100 mL-1. All coffeebrews presented low diterpene contents: 0.05 to 0.16 mg of kahweol and 0.11 to 0.14 mg of cafestol 50 mL-1. Instantcoffee brew showed the lowest content of kahweol and absence of cafestol; this reduction was related to the productionprocess of soluble coffee. Diterpenes content was similar in espresso and paper-filtered brews. The cloth-filtered coffeehad lower solids content, but higher levels of diterpenes (in mg g-1 of solids). Similar cafestol and kahweol contents (mg 50 mL-1)were observed in filtered and espresso brews.